SUBMISSION TITLE: EFFECTS OF USE OF ELECTRONIC MEDIA ON EARLY CHILDHOOD LANGUAGE DEVELOPMENT - Yuli Afmi Ropita Sari (JURNAL KESEHATAN MERCUSUAR, 2019)
This research is motivated by problems that researchers found in a PAUD. The problem at the school was the discovery of children who were addicted to cellphones so that the language skills became late. The purpose of this study is to prove whether electronic media influences children's language development. This research is a descriptive study that uses a qualitative approach. The subjects of this study were two children who were equally addicted to their cellphones. The study was conducted in several stages. The first stage is distributing questionnaires to all parents of children in the school. Furthermore, the data from the questionnaire was processed, after being processed it was obtained research subjects. Then the subject is observed and after that an interview is given to parents. From the results of interviews and observations that have been done, it is found that electronic media influences early language development in children.